The desktop fractal design system - Barnsley, M. F. (Michael Fielding), 1946-; Barnsley, M. F. (Michael Fielding), 1946-; Iterated Systems, Inc. (Boston : Academic Press, 1989)
Provides an introduction to fractal geometry. Teaches the relationship between IFS codes and the fractals which they produce. Processes and outputs IFS codes and allows users to input new fractal images.
Title from disk label.
Handbook by Michael F. Barnsley and Iterated Systems, Inc.
Based on: Fractals everywhere / Michael F. Barnsley.
Write-protected.
Not copy-protected.
Issued also in Macintosh version.
Keywords: Fractals -- Software